Prony Analysis -A Case Study in Eastern Regional Power System in India (London Journal of Engineering Research, 2026)
The stability of the Indian power grid is frequently challenged by Low-Frequency Oscillations (LFOs), particularly in the hydro-dominant Eastern Region, where evacuation corridors are constrained. This paper presents a detailed analysis of a cascade tripping event that occurred on July 7, 2017, involving the 400 kV Teesta-III to Rangpo corridor. Utilizing high-resolution synchro phasor data obtained from Phasor Measurement Units (PMUs), this study characterizes the oscillatory behavior of the grid during the disturbance. While conventional Fast Fourier Transform (FFT) methods are often employed for spectral monitoring, this work employs Prony Analysis due to its superior capability in analyzing non-stationary, transient signals and its ability to directly extract modal damping ratios. The analysis identifies the dominant inter-area and local modes, quantifying their energy, damping percentage, and frequency content. The results demonstrate that specific modes exhibited insufficient damping during the event, contributing to system separation. These findings are subsequently used to derive necessary control parameters for the design of robust Power System Stabilizers (PSS) and oscillation damping filters, aimed at enhancing the dynamic stability of the Eastern Regional Grid.
Keywords: Linear state estimation; Low-frequency oscillations; PMU; Prony analysis; Small-signal stability; Synchrophasor technology; WAMS